Advertising 2006 - Pedersen, B. Martin, 1936-; Kresen, Natalie; Miller, Carla (Graphis, 2005)
The advertising community is premiere show case of print ads from around the world. This Annual is arranged into categories for convienent referencing such as automotive, beauty &cosmetics, food corporat and sports, to name just a few. Over 300 examples of single ads and campaigns are reproduced, along with detailed credits and explanations of each ad and/or campaign that art directors, account managers, and graphic designers sill find this invaluable.